(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
This paper proposes a comprehensive review of the traditional reading that “Cuccagna” is nothing more than a “compensatory myth”, intended as a practical realization of the dream of the poor and the hungry to have plenty to eat effortlessly. On the basis of new documents and linguistic data, the author concludes that the issue of the “myth” is stated only later, in a phase that is chronologically secondary; on the contrary, the idea of “calca / calcagna / Cuccagna” (with evidence not only in language) is brought to the attention of scholars.